Annexins Bridging the Gap: Novel Roles in Membrane Contact Site Formation - Enrich, Carlos; Lu, Albert; Tebar, Francesc; Rentero, Carles; Grewal, Thomas (Frontiers in Cell and Developmental Biology, 2022)
Membrane contact sites (MCS) are specialized small areas of close apposition between two different organelles that have led researchers to reconsider the dogma of intercellular communication via vesicular trafficking. The latter is now being challenged by the discovery of lipid and ion transfer across MCS connecting adjacent organelles. These findings gave rise to a new concept that implicates cell compartments not to function as individual and isolated entities, but as a dynamic and regulated ensemble facilitating the trafficking of lipids, including cholesterol, and ions. Hence, MCS are now envisaged as metabolic platforms, crucial for cellular homeostasis. In this context, well-known as well as novel proteins were ascribed functions such as tethers, transporters, and scaffolds in MCS, or transient MCS companions with yet unknown functions. Intriguingly, we and others uncovered metabolic alterations in cell-based disease models that perturbed MCS size and numbers between coupled organelles such as endolysosomes, the endoplasmic reticulum, mitochondria, or lipid droplets. On the other hand, overexpression or deficiency of certain proteins in this narrow 10-30 nm membrane contact zone can enable MCS formation to either rescue compromised MCS function, or in certain disease settings trigger undesired metabolite transport. In this "Mini Review" we summarize recent findings regarding a subset of annexins and discuss their multiple roles to regulate MCS dynamics and functioning. Their contribution to novel pathways related to MCS biology will provide new insights relevant for a number of human diseases and offer opportunities to design innovative treatments in the future.